Analysis of Legal Protection for Owners of Multiple Land Certificates Issued The Badan Pertanahan Nasional - Dewi Tjandraningsih; Rahul Khan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research objective is to analyze the legal consequences of multiple land certificates with the same object. To study the law for holders of various certificates. To analyze the Supreme Court Decision number 1820K/Pdt/2021. The research method uses a qualitative approach that narrates events that occurred in the field. Data collection techniques through interviews with judges and plaintiffs and documentation studies in the form of archives at the supreme court. The conclusion is that the legal consequences of multiple certificates on land with the same object due to the negligence of the head of the land agency are legal uncertainty in the ownership of various certificates so that multiple certificates can be canceled through a Court Decision because they have permanent legal force (Eintracht van gewijsde), the land agency must is responsible for issuing double certificates and revoking them because they have been declared null and void. Legal protection for land certificate holders, as stated in Government Regulation no. 24 of 1997, Article 19 paragraph (2) letter c, Article 23 paragraph (2), Article 32 paragraph (2), and Article 38 paragraph (2). The certificate is valid as strong evidence; with the Supreme Court's cancellation decision Number 1820 K/Pdt/2021, with Property Rights Certificate no. 535 in Cipatujah Village, legal protection for certificate owners has yet to materialize.